JENIS THEME YANG DITEMUKAN DI RUMAH PERUBAHAN RHENALD KASALI - WULANDARI, MUNTAHANI ZAKIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study tried to find out the types of Theme found in the second scene of Rumah Perubahan Rhenald Kasali eps. Memutar Roda Kereta Api. This study used qualitative method especially document analysis. The data of this study were the utterances of Rhenald Kasali and Ignasius Jonan which contain different kinds of theme namely topical, interpersonal and textual. This study revealed that: (1) Most of the clauses are conveyed in the textual Themes in order to make the message conveyed being in an order way. (2) Some clauses are considered to have topical Theme which allow us to know what the clauses are about. (3) The rest of the clauses belongs to interpersonal Theme which enable the speakers expressing their judgement toward the content of the message.Keywords: Theme, topical Theme, interpersonal Theme, textual Theme, Rumah Perubahan Rhenald Kasali.